The Journey of TAVR - Luis M de la Fuente; Facundo E Peñaloza (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Eighteen years ago, Alain Cribier, MD, and colleagues performed the first transcatheter aortic valve replacement in the year 2002 at Charles Nicolle University Hospital, University of Rouen, France [1]. In the intervening years, Transcatheter Aortic Valve Replacement (TAVR) has completely revolutionize the landscape of Cardiovascular medicine and brought a new spotlight in a treatment previously reign by Surgeons.